Pain, mindfulness, and placebo: a systematic review - Lopes, Alexandra; Sampaio, Rute; Tavares, Isaura (Frontiers in Integrative Neuroscience, 2024)
Introduction Pain is a complex phenomenon influenced by psychosocial variables, including the placebo effect. The effectiveness of mindfulness-based interventions (MBIs) for pain has been demonstrated in experimental studies and systematic reviews, but the mechanisms of action are only starting to be established. Whether the expectations of individuals experiencing pain can be manipulated during MBIs remains to be systematically evaluated, and what role placebo effects might play remains to be explored. Methods To evaluate the literature analyzing placebo effects in MBIs for pain, we performed a systematic review based on searches conducted in PubMed, Web of Science, and SCOPUS databases. Our search revealed a total of 272 studies, of which only 19 studies were included (10 acute pain and nine chronic pain), considering the inclusion and exclusion criteria related to expectations and placebo effects. Results From the 19 included studies, six measured placebo effects only in relation to the pharmacological intervention used in the study and not to an MBI. Discussion The results of the few studies that focused on the placebo effects of the MBIs indicate that placebo and expectations play a role in the MBIs' effects on pain. Although expectations and placebo effects are frequently discussed in the context of mindfulness and pain research, these results show that these factors are still not routinely considered in experimental designs. However, the results of the few studies included in this systematic review highlight a clear role for placebo and expectancy effects in the overall effects of MBIs for both acute and chronic pain, suggesting that routine measurement and further consideration in future studies are warranted. Additional research in this fascinating and challenging field is necessary to fully understand the connection between MBIs, placebo/expectations, and their effects on pain relief.